Preserving Silat Sutera Baja as an Intangible Cultural Heritage through Knowledge Transfer - Irfaniah, Hikmah (Universitas Andalas, 2025)
One of Indonesia's intangible cultural heritages that needs to be preserved is pencak silat. Through knowledge transfer, such cultural heritage is transmitted from one generation to the next. This study aims to elaborate the knowledge transfer process carried out by Silat Sutera Baja Kemayoran Community. This research adopts qualitative case study to gain in-depth understanding of knowledge transfer performed in the community. Research data was obtained through observation and interviews of five informants. Data analysis conveys reduction, data presentation, and conclusions. The results shows that knowledge of Silat Sutera Baja is transferred from Silat instructors to the students through training. The knowledge transfer process takes four stages, including initiation, transfer, ramp-up, and integration. The initiation of knowledge transfer stems from the instructors' motivation to maintain the culture and facilitate students. Transferring knowledge is carried out by giving examples of the movements followed by students, while knowledge other than movement is given by storytelling. At the ramp-up stage, students' knowledge is known by how they show the movements they have mastered, while at the implementation stage, students' knowledge is known when they practice competing. The Silat Sutera Baja community requires more suitable equipment and space for their knowledge transfer practice. Despite these constraints, the instructors can continue passing their knowledge to the younger generation.